Spray PEDOT:PSS coated perovskite with a transparent conducting electrode for low cost scalable photovoltaic devices. (10th November 2015) - Hooper, Katherine; Smith, Ben; Baker, Jenny; Greenwood, Peter; Watson, Trystan
Abstract : Organic–inorganic lead halide perovskite materials are an attractive candidate for low-cost thin-film photovoltaics but in order to successfully rival other technologies, it is critical to focus research on addressing the potential bottlenecks to commercialisation. The conventional hole transporter spiro-OMeTAD and evaporated gold contact are unsuitable for commercialisation due to the cost. This study introduces a method for fabricating perovskite devices without spiro-OMeTAD. Instead, PEDOT:PSS was applied directly to the perovskite material using a carefully controlled spray process. The water hyphen containing PEDOT:PSS used was spray coated onto the perovskite film with careful drying to provide a 55-nm-thick interlayer between the perovskite and the electrode providing hole collection. XRD analysis showed that by controlled application, it was possible to avoid water-induced perovskite degradation. The device was completed using a previously demonstrated transparent conducting adhesive electrode based on vertically orientated channels of PEDOT:PSS within an acrylic adhesive instead of evaporated gold. Fully fabricated devices gave comparable performance to those without spiro-OMeTAD.